A Biophilic Design Approach Resort in the Pari Island of Kepulauan Seribu, Jakarta Province - Fais, Muhammad Noer; Ardhiati, Yuke (Institut Seni Indonesia Bali, 2025)
One of the Jakarta City islands iis the Pulau Pari (Pari Island). eventhough small, it has the natural beauty includes white sandy beaches, coral reefs, and a unique marine ecosystem. Unfortunately, the remarkable tourism potential of Pari Island has not been matched with adequate facilities. The lack of proper accommodations and poorly organized tourist areas are some of the main issues. Therefore, this study in qualitative method aims to design a resort hotel using a biophilic approach, which integrates natural elements into architectural design. The biophilic concept was chosen to respond to the tropical island climate of Pari Island by offering architectural solutions that connect the built environment with nature. by employee the metaphoric in architecture form. Based on literature studies, the biophilic design approach contritbuted to built environments fostering a strong connection between humans and nature. by accomadated thie biophilic design approach is implemented through natural lighting, incorporation of water elements, and the integration of vegetation.